2011
DOI: 10.1038/bmt.2011.122
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic score with pretransplant serum ferritin and disease status predicts outcome following reduced-intensity SCT

Abstract: Abbreviations: MDS ¼ myelodysplastic syndrome; NR ¼ non-remission; RA ¼ refractory anemia; RAEB ¼ refractory anemia with excess blasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…We and other groups have previously demonstrated that high serum ferritin levels before HSCT may reduce OS and EFS after HSCT. [1][2][3][4][5][6][7][8][21][22][23][24] To the best of our knowledge, the present study is the first to confirm these findings using a large prospective cohort.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We and other groups have previously demonstrated that high serum ferritin levels before HSCT may reduce OS and EFS after HSCT. [1][2][3][4][5][6][7][8][21][22][23][24] To the best of our knowledge, the present study is the first to confirm these findings using a large prospective cohort.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have demonstrated that pretransplant iron overload, defined as elevated serum ferritin levels, is associated with worse OS, disease-free survival and non-relapse mortality (NRM) and with an increased risk of infection in patients undergoing allogeneic HSCT. [1][2][3][4][5][6][7][8][9] Liver dysfunction caused by iron overload 10 and neutrophil dysfunction with an increase in non-transferrin-bound iron levels 11,12 may have a negative impact on HSCT outcomes. However, most previous studies involved retrospective analyses of patients with heterogeneous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To further stratify patients in clinical studies, a scoring system that consists of SF and disease status at transplantation might be valuable to predict the outcomes. 6,7 From this study, we cannot deduce that the adverse prognostic impact of pretransplantation HF is associated with iron overload. To provide definitive answers regarding the role of iron overload in HSCT, we should in future, as Dr Armand suggested, perform studies that incorporate direct measurements of parenchymal and labile iron.…”
mentioning
confidence: 68%
“…Several recent reports demonstrated that IO is an adverse prognostic factor for patients undergoing allo-HSCT [1,17,22,36,59,[62][63][64][65][66]. In a retrospective cohort of 114 AML and MDS patients, the OS rate at 5 years was found to be significantly better in patients with ferritin levels < 1000 ng/ml [1].…”
Section: Prognostic Role Of Iron Overload In Stem Cell Transplantationmentioning
confidence: 93%